Correlation between shear-wave velocity and topographic slope - Fong, Rodney. (2011)
The method of using topography as a proxy for average shear wave velocity of upper 30 meters has become an increasingly interesting topic for seismic research mainly because of the advantages it offers such as low cost, simplicity, automation, and its ability to generate extensive maps with first order assessment of seismic site conditions. This method is largely based on the correlation of gradient slope and Vs30. In this project, Vs30 values are obtained from Standard Penetration Test (SPT) N values of borehole logs. These borehole investigations were conducted across Singapore where their soil profile data are available. Next, calculation and tabulation of Vs30 from all 531 borehole logs were made. SPT N values and their various depths were used to obtain the computed Vs30 values; the computations were based on empirical correlation equations for SPT N & Vs30. These SPT N correlations were formulated in a way that they are catered for different soil types such as fill (sand and silt), alluvium deposits (sand), alluvium and marine clay, residual soil and completely weathered sedimentary rock, and residual soil and completely weathered granite. After all computed Vs30 values are obtained, a database was constructed from these computed Vs30 values and their corresponding topographic slope, which was derived from elevation data and the ArcGIS software. The database is than manipulated to formulate different correlations between topographic slope and Vs30.